2013
DOI: 10.1186/1471-244x-13-165
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function in bipolar disorder: a comparison between bipolar I and II disorder and matched controls

Abstract: BackgroundCognitive deficits have been documented in patients with bipolar disorder. Further, it has been suggested that the degree and type of cognitive impairment differ between bipolar I and bipolar II disorder, but data is conflicting and remains inconclusive. This study aimed to clarify the suggested differences in cognitive impairment between patients with bipolar I and II disorder in a relatively large, clinically stable sample while controlling for potential confounders.Methods67 patients with bipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
53
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 37 publications
(43 reference statements)
9
53
0
2
Order By: Relevance
“…However, Dittmann et al (2008) and Chaves et al (2011) found no neuropsychological differences between these two diagnosis types. The fact that patients with BD Type-I have full-blown manic episodes and more psychotic symptoms could contribute to these inconsistent findings (Palsson et al, 2013), as some authors found indeed a significant association between psychotic symptoms and cognition (Aminoff et al, 2013;Bora et al, 2011), while others did not (Brissos et al, 2011). Furthermore, individuals diagnosed with BD Type-I are more often treated with antipsychotics compared to BD-II, which could contribute to cognitive impairments in this patient group (Arts et al, 2011;Jamrozinski et al, 2009;Palsson et al, 2013;Torrent et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Dittmann et al (2008) and Chaves et al (2011) found no neuropsychological differences between these two diagnosis types. The fact that patients with BD Type-I have full-blown manic episodes and more psychotic symptoms could contribute to these inconsistent findings (Palsson et al, 2013), as some authors found indeed a significant association between psychotic symptoms and cognition (Aminoff et al, 2013;Bora et al, 2011), while others did not (Brissos et al, 2011). Furthermore, individuals diagnosed with BD Type-I are more often treated with antipsychotics compared to BD-II, which could contribute to cognitive impairments in this patient group (Arts et al, 2011;Jamrozinski et al, 2009;Palsson et al, 2013;Torrent et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Another often reported finding is that patients diagnosed with BD Type-I have more cognitive deficits than patients with BD Type-II (Aminoff et al, 2013;Ancin et al, 2013;Palsson et al, 2013;Torrent et al, 2006). However, Dittmann et al (2008) and Chaves et al (2011) found no neuropsychological differences between these two diagnosis types.…”
Section: Introductionmentioning
confidence: 98%
“…The disorder is not only associated with premature death, significant disability and impaired psychosocial functioning, 1 but also with cognitive impairments. 2 Summarizing previous imaging studies of patients with BD, recent meta-analyses and review articles have concluded that these patients demonstrate abnormalities primarily in frontal lobe regions, such as abnormally low volumes not only in the anterior cingulate cortex (ACC), medial and inferior frontal, orbitofrontal, ventral and dorsolateral prefrontal cortices, but also in the temporal and insular cortices. [3][4][5][6][7][8][9] There are 2 established subtypes of BD: type I and type II.…”
Section: Introductionmentioning
confidence: 99%
“…The first-line mood-stabilizing treatments include lithium, divalproex, olanzapine, and lamotrigine (the latter mainly for those with mild manias) (Yatham et al, 2009). BD has also been coupled to cognitive impairment including reduced abilities in executive function and verbal memory (Martinez-Aran et al, 2000;Zarate et al, 2000;Martinez-Aran et al, 2005;Robinson et al, 2006;Sanchez-Moreno et al, 2009;Palsson et al, 2013). Structural imaging studies have suggested that the decline in cognitive function is associated with morphological abnormalities of the brain (Altshuler et al, 1995;McDonald et al, 2004;Kempton et al, 2008;Konarski et al, 2008), and that the number of manic episodes is associated with decreased gray matter in dorsolateral prefrontal cortex (Ekman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%